Semiotic Citizenship and the Construction of Belonging in Multilingual Public Spaces - Aulia Rahman (LIER: Language Inquiry & Exploration Review, 2024)
Purpose: This study investigates how semiotic citizenship is enacted and experienced within multilingual public spaces, focusing on how language, visibility, and affect intertwine to construct belonging in the urban environment. It explores how individuals negotiate recognition and participation through linguistic and visual signs that populate the city’s semiotic landscape. Subjects and Methods: The research was conducted across three key urban sites a traditional market, a transportation terminal, and a municipal plaza selected for their contrasting semiotic ecologies. Using a qualitative ethnographic design grounded in semiotic landscape analysis, data were collected through visual documentation, participant observation, and semi-structured interviews with twenty-five participants including traders, migrants, residents, and municipal officers. The analysis combined multimodal discourse analysis and thematic coding to interpret how signs, languages, and emotions converge to produce symbolic belonging. Results: Findings reveal that multilingual signs act as semiotic performances of citizenship, where linguistic hierarchies, creative hybridity, and emotional recognition coexist. Formal spaces reproduce institutional authority through standardized language, while informal environments allow vernacular and hybrid expressions to emerge as acts of grassroots visibility. Participants expressed feelings of inclusion, remembrance, and shared authorship through the visibility of their languages in public spaces. Conclusions: Semiotic citizenship operates as an affective and participatory practice rather than a formal status. Belonging is not merely spoken but inscribed in the multilingual textures of urban life, where visibility itself becomes a moral act of recognition. The city thus emerges as a semiotic democracy continually rewritten through the languages of its people.